Novel anterior cruciate ligament graft fixation device reduces slippage - Lopez MJ (Dove Medical Press, 2013)
Mandi J Lopez,1 Allen Borne,2 W Todd Monroe,3 Prakash Bommala,1 Laura Kelly,1 Nan Zhang11Laboratory for Equine and Comparative Orthopedic Research, Department of Veterinary Clinical Sciences, School of Veterinary Medicine, Louisiana State University, Baton Rouge, 2Louisiana State University, New Orleans Health Sciences Center, School of Medicine, New Orleans, 3Department of Biological and Agricultural Engineering, Agricultural Center, Louisiana State University, Baton Rouge, LA, USAAbstract: Clinically significant laxity occurs in 10%–30% of knees after anterior cruciate ligament reconstruction. Graft slippage and tension loss at the hamstring graft tibial fixation site during and after reconstruction surgery contribute to postoperative joint laxity and are detrimental to long-term knee stability and graft properties. Limiting graft slippage will reduce associated complications. We sought to compare the in vitro mechanical properties and in vivo joint stabilization, postoperative limb use, and graft incorporation of the novel GraftGrab™ (GG) device designed to reduce hamstring graft tibial fixation slippage with the commercially available bioabsorbable Bio-Post™ and spiked washer (BP). Mechanical testing was performed on canine tibia-hamstring graft constructs to quantify initial fixation properties. In vivo joint stabilization, postoperative limb use and graft incorporation of hamstring graft reconstructions were determined in a canine model. Outcomes included tibial translation and ground reaction forces preoperatively and 4 and 8 weeks postoperatively, three-dimensional graft and bone tunnel dimensions at the latter two time points, and graft-bone microstructure, as well as mechanical properties 8 weeks after implantation. Immediately after fixation, all grafts slipped from the BP constructs versus about 30% of GG constructs. In vivo limb use remained low, and tibial translation increased with time in the BP cohort. These results together confirm that initial graft slippage is lower with GG versus BP extracortical hamstring graft tibial fixation. In addition, postoperative recovery and joint stability are more consistent with the GG. This information supports the GG as an alternative to extracortical tibial hamstring graft fixation that has procedural advantages over current implants and reduces graft failure from slippage.Keywords: cruciate, implant, bioabsorbable, canine, graft, tibia